Tingkat Keterampilan Dasar Futsal Siswa SD Negeri Pucangan 02 Kartasura - Hidayat, Muhammad Taufiq; Warthadi, Anugrah Nur; Sistiasih, Vera Septi; Kurniawan, Ardhian Tomy (Universitas Hamzanwadi, 2024)
The purpose of this study was to assess the level of basic skills of playing futsal in students at SDN Pucangan 02 Kartasura. This type of research is quantitative descriptive research. The method used is a survey with test and measurement techniques. Through tests and measurements will obtain objective data. The research subjects were students of SDN Pucangan 02 Kartasura class totaling 20 students consisting of 20 male students. Data collection was done through observation and tests. Data analysis was quantitatively descriptive. The results of the study were the level of skills in playing futsal for students of SDN Pucangan 02 Kartasura in 2023/2024 was declared “good” as many as 11 students (55%). This means that the level of futsal skills of futsal extracurricular participants is at a good level, while the average value of 110.2000 lies in the “medium” interval. Furthermore, this can provide consideration for coaches or trainers in order to improve physical and psychological quality, develop strategies, techniques and playing patterns and improve the quality and psychological abilities of futsal extracurricular participants. So that the ability and skills to play futsal for students of SDN Pucangan 02 Kartasura in 2023/2024 can continue to increase.